Electrospinning of epoxy fibers: Mechanical properties and failure mechanisms - Mark Shneider; Xiaomeng Sui; Iddo Pinkas; Ulyana Shimanovich; Israel Greenfeld; Daniel Wagner (eXPRESS Polymer Letters)
Electrospinning is a widely used technique for manufacturing nanofibers from polymers. The formation of continuous fibers during the drawing of a viscous solution typically depends on entanglements between polymer chains, making thermoplastics the preferred choice. In this study, we have shown that thermosetting polymers such as epoxy, which have crosslinked covalent bonds, can also be electrospun. The resulting fibers have diameters ranging from 150 nm to 6 μm. Tensile mechanical properties of fibers with diameters varying between 410 nm and 4 μm are compared with those of molded epoxy bulk. The electrospun fibers exhibit approximately 555% higher strength, 300% greater stiffness, and a strain of about 109% compared to the equivalent properties of bulk epoxy. When compared with brittle molded bulk, these fibers showed ductile properties. We also observed a correlation between the fiber diameter and the mechanical properties. The molecular morphology of the fibers was monitored and analyzed using polarized micro-Raman spectroscopy to detect molecular orientation. A comparison with epoxy fibers of different diameters from previous studies was conducted to better understand the size effect. This study shows, explains and models the evolution of epoxy molecular morphology from the solution (soft matter) to fiber (solid-state), explaining the transition from brittle to ductile in epoxy fibers, and clarifying the molecular mechanisms that lead to improved mechanical properties.